2020
DOI: 10.1177/1533033820934130
|View full text |Cite
|
Sign up to set email alerts
|

MiR-7 Functions as a Tumor Suppressor by Targeting the Oncogenes TAL1 in T-Cell Acute Lymphoblastic Leukemia

Abstract: Background: T-cell acute lymphoblastic leukemia is a hematologic malignancy characterized by T-cell proliferation, and in many cases, the ectopic expression of the oncogenic transcription factor T-cell acute lymphocytic leukemia protein 1 (TAL1). MicroRNA-7 has been shown to play a critical role in proliferation, migration, and treatment sensitivity in a diverse array of cancers. In this study, we sought to establish a novel link between microRNA-7 and T-cell acute ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…In addition, miR-7-5p can increase the sensitivity of breast carcinoma cells to adriamycin after inhibiting the epidermal growth factor (EGF) receptor/PI3K signaling pathway [ 43 ], and can inhibit the proliferation and metastasis of osteosarcoma cells by targeting insulin-like growth factor 1 receptor [ 44 ]. Another study revealed that miR-7-5p inhibits the proliferation of T-cell acute lymphoblastic leukemia by targeting the oncogene T-cell acute leukemia protein 1 [ 45 ]. More essentially, the anticancer effects of miR-7-5p have been reported in other carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-7-5p can increase the sensitivity of breast carcinoma cells to adriamycin after inhibiting the epidermal growth factor (EGF) receptor/PI3K signaling pathway [ 43 ], and can inhibit the proliferation and metastasis of osteosarcoma cells by targeting insulin-like growth factor 1 receptor [ 44 ]. Another study revealed that miR-7-5p inhibits the proliferation of T-cell acute lymphoblastic leukemia by targeting the oncogene T-cell acute leukemia protein 1 [ 45 ]. More essentially, the anticancer effects of miR-7-5p have been reported in other carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that there are several p53-dependent miRNAs induced in response to DNA damage in CLL, proposing that the miRNoma for the identification of the dependent DNA damage response machinery stems from p53 [ 118 ]. In ALL (acute lymphoblastic leukemia) of T lymphocytes, it was reported that the overexpression of miR-7 is capable of suppressing TAL1 levels and reducing growth, mobility, and migration, as well as promoting the induction of apoptosis, allowing it to play a potential role as tumor suppressor [ 119 ]…”
Section: Mir-7 In Cancermentioning
confidence: 99%
“…In T-ALL, miR-7 was found to bind to TAL1 , coding for T-cell acute lymphocytic leukaemia protein. In T-ALL, expression of miR-7 is often attenuated, while TAL1 expression is increased and solicitates cell proliferation [ 80 ]. In Non-Hodgkin lymphoma cells, miR-7 regulates migration and chemoresistance through KLF4 and YY1 [ 108 ] and miR-7 downregulation can increase the aggressiveness of follicular lymphoma by FasL upregulation in macrophages which modulate immunosuppressive stroma [ 174 ].…”
Section: Mir-7 Roles In Leukaemiamentioning
confidence: 99%